Corelation of Perceived Social Support and Psychological Hardness with Perceived Stress and Aggression in Retired Veterans - L. Ebrahimi; F. Moradi (Afarand Scholarly Publishing Institute, 2018)
Aims: The purpose of this study was to investigate the role of perceived social support and psychological hardness in perceived stress and aggression of retired veterans. Instrument and Methods: This study is a descriptive correlational which was done in Bijar city in 2017. The statistical population of the study consisted of all retired veterans of Bijar city at 92 samples were selected through an available sampling method based on Morganchr('39')s table and responded to perceived social support, hardness, perceived stress and aggression questionnaires. Data were analyzed by Pearson correlation, multiple regressions and SPSS 22 software. Findings: There was a significant negative corelation between perceived social support and perceived stress (r=-0.26; p<0.05), perceived social support and aggression (r=-0.22; p<0.05), Also, there was a negative and significant corelation between perceived stress and perceived stress (r=-0.30; p<0.05), hardness and aggression (r=-0.27; p<0.05). Finally, there was a significant positive correlation between perceived stress and aggression (r=0.52; p<0.05). Perceived social support and psychological hardness were able to significantly affect 33% of the variance of perceived stress in retired Veterans and significantly predict 49% of the variance of aggression in retired Veterans variable. Conclusion: There is a correlation between perceived social support and psychological Hardness with perceived stress and aggression of retired veterans, in a way that perceived social support and psychological hardness can be effective in reducing the stress and aggression of retired veterans and should be considered as effective moderating factors in stress and aggression.   Keywords [https://www.ncbi.nlm.nih.gov/mesh/68012944];  [https://www.ncbi.nlm.nih.gov/mesh/68006244];  [https://www.ncbi.nlm.nih.gov/mesh/68013315];  [https://www.ncbi.nlm.nih.gov/mesh/68000374];  [https://www.ncbi.nlm.nih.gov/mesh/68014728]